Menguji Asas Presumtio Iustae Causa dalam Sengketa Tata Usaha Negara : Indonesia - Sukri, Indah (DIKTUM: Jurnal Syariah dan Hukum, 2022)
The principle of Presumtio Iustae Causa is a part of State Administrative Decree implementated in resolving state administrative disputes. This principle means that a State Administrative Decision should be valid consideration. It could be make the validity lost when the new decision one cancels or revokes the old decision. The paper purposed the establishment of State Administrative Courts, to provide protection for the rights of the people as originately from personal rights as well as to provide protection for the community rights of society based on the common interests of community. This qualitative research applied a normative juridical legal method. The study resulted that a government obligated to promote the general welfare as stated in the constitutional mandate. In carrying out this obligation, the government has to take Administrative Law Enforcement actions.